Looking into the life of technology-dependent children and their caregivers in Korea: lifting the burden of too many responsibilities - Yu Hyeon Choi; Min Sun Kim; Cho Hee Kim; In Gyu Song; June Dong Park; Dong In Suh; Hyung-Ik Shin (BMC, 2020)
Abstract Background The number of technology-dependent children (TDC) is increasing in South Korea, but available healthcare services after their discharge are poor. This study aimed to examine how TDC and caregivers live at home and identify their difficulties and needs regarding home care with few services to support them. Methods This cross-sectional study was conducted in a tertiary hospital for children in South Korea. A self-reported questionnaire was completed by primary caregivers of TDC who were younger than 19 years and had been dependent on medical devices for more than 3 months. Technologies included home mechanical ventilation, oxygen supplementation, suction equipment, enteral feeding tube, and home total parenteral nutrition. Patterns of healthcare use and home care of TDC and caregivers' perception toward child were assessed. Results A total of 74 primary caregivers of TDC completed a self-reported questionnaire. About 60% children were aged under 5 years. There were 31.1% children who required both respiratory and nutritional support. On average, caregivers took care of a child for 14.4 (±6.1) hours, slept for 5.6 (±1.6) hours, and spent 2.4 h per day on personal activities. Children used hospital services for 41.3 (±45.6) days in 6 months, and most (78.1%) were transported through private car/ambulance. Participants (75.6%) reported taking more than an hour to get to the hospital. More than 80% of caregivers responded that child care is physically very burdensome. The only statistically significant relationships was between economic status and financial burden (p = 0.026). Conclusions Caregivers of TDC reported having significant time pressure regarding childcare-related tasks, insufficient time for personal activities, and inefficient hospital use because of inadequate medical services to support them in South Korea. Thus, it is necessary to support caregivers and develop a home care model based on current medical environment.